Roadmap to Self-Serving Assets in Civil Aerospace - Brintrup, Alexandra Melike; Ranasinghe, D. C.; Kwan, S.; Parlikad, A.; Owens, K. (Cranfield University Press, 2009)
The “intelligent object” paradigm first occurred in holonic manufacturing, where objects managed their production. The “self-serving asset” is a further evolution of those early concepts from manufacturing to usage phase. The usage phase bestows a different set of requirements including maximisation of the asset’s life-in-service and benefits to the asset’s stakeholders. Addressing these requirements with a selfserving asset may lead to more streamlined decision-making in service operations, reduce erroneous or suboptimal decisions, and enable condition-based maintenance. We present a future direction for service systems by considering self-serving assets in the aerospace industry, and outline a technology roadmap for the transformation.
Organised by: Cranfield University
Keywords: Multi-agent systems; Self-serving asset; Intelligent object; Aerospace service supply chain